RELATIONSHIP OF MOTIVATION WITH SELF PROTECTION BEHAVIOR IN FUNGUS TB FAMILY IN UMBULHARJO I PUSKESMAS YOGYAKARTA - Istichomah, Istichomah; Khoeriyah, Salis Miftahul (Jurnal Kesehatan Samodra Ilmu (JKSI), 2019)
Background: The World Health Organization (WHO) states that in 2015 there were around 1.4 million people worldwide who died of pulmonary TB. The risk of transmission of pulmonary TB every year is increasing. The family is the closest person who has a high risk of contracting TB. Therefore families with pulmonary TB patients must have motivation in the effort of self protection or prevention of transmission to family members. Family motivation greatly determines the success of treatment, especially in preventing transmission, because if the behavior of the client's family diagnosed with pulmonary TB understands what he or she is actually doing, then the family is indirectly able to protect himself and other family members. Objective: This study aims to determine the relationship between motivation and self-protection behavior in families with pulmonary TB patients in Yogyakarta's Umbulharjo I Health Center. Methods: This research is a quantitative study with analytical survey research design and cross sectional approach, which was conducted in September 2017. The population in this study were families of pulmonary TB patients who were in the Umbulharjo I Health Center Yogyakarta, totaling 32 people, the sampling technique used sampling totals. Analysis of the data used is Kendal Tau, to determine motivation with self-protection behavior in families with pulmonary TB patients. Results: The results show kendall correlation value of P-Value 0.004 <α = 0.05. According to Sugiyono (2010), it is explained that if the probability is less than 0.05, then Ho is rejected, which means there is an influence between the two variables. So that the analysis results with p value (probability value) of 0.004 are smaller than 0.05. These results indicate that Ho is rejected and Ha is accepted, so the hypothesis of this study states that there is a relationship between motivation and self-protection behavior of families with pulmonary TB sufferers. A positive correlation coefficient indicates that the higher a person's motivation, the more someone will lead to positive behavior. Conclusion: The motivation of families with pulmonary TB in Yogyakarta's Umbulharjo I Health Center mostly had moderate motivation of 18 people (56.2%). The self protection behavior of families with pulmonary tuberculosis sufferers at the Umbulharjo I Health Center in Yogyakarta partly had a positive self protection behavior of 28 people (87.5%).